Gastroenteritis Norovirus dan Perkembangan Vaksin Norovirus: Analisis - I Kadek, Aribowo; Miyardi, Ade Sithanaya (Cermin Dunia Kedokteran, 2025)
Viral gastroenteritis is responsible for millions of diarrhoea cases annually. Norovirus is currently reported to be the second leading cause of acute diarrhoea worldwide, after rotavirus, in all paediatric age groups in both developed and developing countries. Norovirus is a single-stranded RNA virus belonging to the Caliciviridae family. The largest human strain belongs to genogroup II, genotype 4 (II.4). Transmission is primarily faecal-oral with humans as the principal host; the virus itself has a very low infectious dose, persists across diverse temperatures and surfaces, and can be shed pre-symptomatically, enabling rapid spread. Clinical features include nausea, vomiting, abdominal cramps, and diarrhea, with heightened dehydration risk among young children, older adults, and immunocompromised individuals. To date, norovirus vaccine development still encountered difculties, including the complex nature of norovirus, human immune response, virus culture, and limited animal models for vaccine testing. Currently, several vaccines are still in the pre-clinical stage. Vaccine development needs to be accelerated while maximizing prevention of norovirus infection.